2020
DOI: 10.22441/jte.2020.v11i1.007
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Inertial Measurement Unit (IMU) MPU- 6050 3-Axis Gyro dan 3-Axis Accelerometer pada Sistem Penstabil Kamera (Gimbal) Untuk Aplikasi Videografi

Abstract: Otomasi sistem merupakan penggabungan antara mekanik, dan software menjadi sebuah fungsi tertentu sebagai cara untuk mempermudah kehidupan manusia. Otomasi sistem pada bidang fotografi memiliki prospek yang cukup menarik untuk dikembangkan peralatan otomatis yang menunjang keperluan fotografi. Dengan adanya sistem penstabil kamera (gimbal), videografer bisa mengambil gambar dengan hasil kualitas yang memadai di tempat manapun tanpa harus memikirkan getaran maupun gerakan yang akan mengganggu kamera saat pengam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some of the failures that occur in the experiment can be caused by: (i) the angle range which is not in accordance with the set limit, so that changes in angles outside the range will not be detected by the Gyroscope, (ii) different heights for each person are also differentiating angle ranges, as well as (iii) delivery range distances exceeding the maximum limit of the device will cause the signal to be undelivered. In this study, the HC-12 wireless module used has a longer data transmission distance than that in the previous study (HC-04), which can only transmit data at a maximum distance of 15 meters [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the failures that occur in the experiment can be caused by: (i) the angle range which is not in accordance with the set limit, so that changes in angles outside the range will not be detected by the Gyroscope, (ii) different heights for each person are also differentiating angle ranges, as well as (iii) delivery range distances exceeding the maximum limit of the device will cause the signal to be undelivered. In this study, the HC-12 wireless module used has a longer data transmission distance than that in the previous study (HC-04), which can only transmit data at a maximum distance of 15 meters [6].…”
Section: Resultsmentioning
confidence: 99%
“…The deaf also require help from the others in daily life, including in worship, such as praying in congregation for the Muslims. Following the movement of the Imam in congregational prayers, especially in the position of getting up from prostration, is a problem experienced by the deaf [5], [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this research can be concluded that the application of the Gyro Accelerometer Sensor to Regulate Respiration Based on Delphi Based Inhales and Exhales (Sensor Position Parameters) has been successfully created and can be used properly. This means that the tool can apply the use of the Gyro Accelerometer Sensor to measure respiration at the time of inhale, exhale and there is a difference in the value of respiration at the placement of Sensor 1, Sensor 2 and Sensor 3 [30][13] [31]. The placement of 3 different sensors in this study has an error value that tends to be low because it has a difference.…”
Section: Discussionmentioning
confidence: 99%